A Method for Identifying Warm Fronts in Eurasia - Qin, Yujing; Wang, Jiachen; Lu, Chuhan; Feng, Mengru (International journal of climatology, 2025)
ABSTRACT Warm fronts often trigger significant weather changes, which also play a role in many extreme weather incidents. Therefore, it is crucial to understand the location and characteristics of warm fronts to accurately forecast weather changes. However, warm fronts are more difficult to identify than cold fronts on average, since the gradients can be weaker and shallower. This paper proposes a new objective method for identifying warm fronts in the Eurasia region using ERA‐5 hourly reanalysis data. The method uses the appropriate thermal front parameter and warm advection threshold to identify the potential warm frontal zone, then determines the corresponding warm boundary according to the predominant wind direction within the frontal zone, and finally locates the warm front line along the warm boundary. In various weather processes, the location and shape of the objective warm front correspond well with the distribution of weather systems and meteorological elements, indicating the effectiveness of the method. Meanwhile, the high agreement between objective and manual warm fronts further supports the reliability of the method. Furthermore, this method is applied to the long‐term datasets covering Eurasia, enabling an exploration of the climatological characteristics of warm fronts in the region. The study reveals distinct seasonal patterns in warm front frequency, with the highest frequency occurring during winter and the lowest during summer. Warm fronts are notably active in Europe, the Siberian Plain, the Northeast China Plain extending to the Western Pacific during winter, spring, and autumn. The dataset of warm fronts produced by this method proves valuable for climate change research. This paper proposes a new objective method for identifying warm fronts in the Eurasia region and validates its effectiveness through various weather processes and long‐term identification results. Meanwhile, the method has been applied to long‐term data over Eurasia to obtain the climatological characteristics of warm fronts in the region.